Bottom-Up Fabrication of PEG Brush on Poly(dimethylsiloxane) for Antifouling Surface Construction. (15th June 2016) - Tang, Junmei; Han, Yuemei; Chen, Hao; Lin, Quankui
Abstract : Poly(dimethylsiloxane) silicones have found many applications in biomedical devices, whereas their surface hydrophobicity always brings about unexpected bioadhesion, causing complications of the implanted biomedical devices. In this work, surface-initiated reversible addition-fragmentation chain transfer (SI-RAFT) polymerization was utilized to generate PEG brushes on silicone surface, obtaining highly hydrophilic surface coatings. Such PEG brush coated silicone presents excellent antifouling to protein, cells, and bacteria, which may have great potential in implantable biomaterial surface modifications.